Where to cross? New insights into the location of meiotic crossovers. Issue 7 (July 2015) - Mézard, Christine; Tagliaro Jahns, Marina; Grelon, Mathilde
Highlights Crossovers (COs) are essential to the proper segregation of chromosomes at meiosis. CO distribution along the chromosomes is tightly controlled. CO distribution along the chromosomes is a characteristic of each species. CO localization mirrors only partially meiotic double-strand breaks activity. CO landscape of a given species is the result of several levels of regulation.